2022
DOI: 10.1609/aaai.v36i2.20130
|View full text |Cite
|
Sign up to set email alerts
|

Dual Contrastive Learning for General Face Forgery Detection

Abstract: With various facial manipulation techniques arising, face forgery detection has drawn growing attention due to security concerns. Previous works always formulate face forgery detection as a classification problem based on cross-entropy loss, which emphasizes category-level differences rather than the essential discrepancies between real and fake faces, limiting model generalization in unseen domains. To address this issue, we propose a novel face forgery detection framework, named Dual Contrastive Learning (DCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 21 publications
0
34
1
Order By: Relevance
“…Based on this idea, we can force the model to focus on intra-inconsistency using pseudo annotations. In addition, different from the previous works [27,1] which specially design a module to obtain the consistency-related representation, we find that Vision Transformer [5] naturally provides the consistency representation from the attention map among patch embeddings, thanks to their self-attention mechanism. Therefore, we apply it to build the detection network and propose two key components: UPCL (Unsupervised Patch Consistency Learning) and PCWA (Progressive Consistency Weighted Assemble).…”
Section: Introductioncontrasting
confidence: 76%
See 4 more Smart Citations
“…Based on this idea, we can force the model to focus on intra-inconsistency using pseudo annotations. In addition, different from the previous works [27,1] which specially design a module to obtain the consistency-related representation, we find that Vision Transformer [5] naturally provides the consistency representation from the attention map among patch embeddings, thanks to their self-attention mechanism. Therefore, we apply it to build the detection network and propose two key components: UPCL (Unsupervised Patch Consistency Learning) and PCWA (Progressive Consistency Weighted Assemble).…”
Section: Introductioncontrasting
confidence: 76%
“…Some works focused on inevitable procedures in forgery, such as affine warping (DSP-FWA [14]) and blending (Face X-ray [12]). While others observed that certain type of inconsistency exists in different kinds of forgery videos, such as temporal inconsistency (LipForensics [7], FTCN+TT [35]) and intra-frame inconsistency (Local-related [1], PCL+I2G [34], Dual [27]). However, in order to learn corresponding artifacts or inconsistency cues, Face X-ray [12] and PCL+I2G [34] try to generate the large-scale datasets with annotated forged location for their pixel-level supervised learning.…”
Section: Face Forgery Detectionmentioning
confidence: 99%
See 3 more Smart Citations